Ambivalensi Peran Birokrasi Negara Sebagai Pendukung Perjuangan Kelompok Perempuan dan Politik Gender Penguasa - Sofa Marwah (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2011)
The Strugle Promote women requires cooperation of women groups with the state, throughthe device or the National Machineries, namely the state bureaucracy from top to bottom level. But there is ambivalence in this cooperation. On the one hand, gender mainstreaming mechanisms supported by National Machineries proved able to build a stable alliance with civil society group of women, especially in countries that have stable political economy. However, in developing countrie, the situation is likely to varry even pessimistic. Cooperation with the state has made a restriction to the changes, as well as to the choice of fighting for women's issues. As quoted Shirin M. Rai, the women's movement needs to work